Political Identity and Citizenship Participation (Representatives) in Politics by Minangkabau Women in Post-2019 Election - Sri Zul Chairiyah (Politik Indonesia: Indonesian Political Science Review)
This research aimed to describe the identity politics and citizenship of Minangkabau women, towards the political participation (representation) of Minangkabau women in the post-2019 election. Minangkabau women have 2 identities, in adat (matrilineal system) women have rights that are equal to men in decision making, while in religion (patrilineal system), women are not one of the main elements in decision making. In citizenship, community still applies a patriarchal culture that is rooted and dominates. These two identities have a major influence on the political representation of Minangkabau women, where identity politics and citizenship are attempts to understand the relationship of these two concepts to the involvement of Minangkabau women in political representation in each election. The research used aqualitative method with individual analysis. This research was conducted in West Sumatra Province. These two factors influence the political representation of Minangkabau women in West Sumatra. The temporary conclusion showed that the low political representation of Minangkabau women in legislative institutions is not because of identity politics but because of patriarchal culture is still rooted and dominates in the community especially in West Sumatra.